2012
DOI: 10.1007/s11033-012-2291-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of dehydrin gene from Ammopiptanthus mongolicus

Abstract: Based on the sequence of an expressed sequence tag, the full-length cDNA of 1,008 nucleotides was cloned from Ammopiptanthus mongolicus by rapid amplification of cDNA ends. It was designated as AmDHN, encoding a protein of 183 amino acids. The calculated molecular weight of the AmDHN protein is 18.4 k Da, and theoretical isoelectric point is 5.78. The AmDHN localized in nucleus. Under normal growth conditions, differential expression of AmDHN exhibited that the expression was the highest in seeds and the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…So we speculated that dehydration gene involved in stress resistance of plants. Previous studies showed that AmDHN was induced by drought, osmotic stress and ABA (Sun et al 2013). Our findings found that expressions of CBF2, CBF3, CAS17, and ProDH in transgenic alfalfa increased significantly after being treated with 4 °C, as compared Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…So we speculated that dehydration gene involved in stress resistance of plants. Previous studies showed that AmDHN was induced by drought, osmotic stress and ABA (Sun et al 2013). Our findings found that expressions of CBF2, CBF3, CAS17, and ProDH in transgenic alfalfa increased significantly after being treated with 4 °C, as compared Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Among these, dehydrins (DHNs), also known as late embryogenesis abundant (LEA) proteins have been evaluated. The accumulation of DHNs in plants may be induced by abscisic acid (ABA) or any environmental influence that causes dehydration of the cells, such as freezing or other low temperatures, heat, high salinity, or drought (Nylander et al 2001;Wisniewski et al 2006;Sun et al 2013). It is proposed that DHNs can protect proteins and membranes from unfavorable structural changes caused by dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ecological importance and high academic value, A. mongolicus has become a good model for studying plants under abiotic stress conditions. Most studies have focused on morphological characteristics, physiological responses under abiotic stress conditions (Xu et al, 2002), and on several candidate genes involved in various stress responses (Wei et al, 2011a;Sun et al, 2013;Gu and Cheng, 2014). However, there are very few reports on the diversity of germplasm resources and molecular markers of A. mongolicus.…”
Section: Introductionmentioning
confidence: 99%
“…AmDHN could be induced by PEG-6000 and drought treatments, and the expression of AmDHN could be improved under water deficit conditions. At the same time, the drought resistances of transgenic plants overexpressing AmDHN were improved (Sun et al, 2013). In addition, the drought-related DHNs PaDhn1 and PaDhn6 were strongly up-regulated in stem bark and current-year needles in response to drought (Eldhuset et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Among the droughtresistant gene candidates, the major proteins of the Late Embryogenesis Abundant (LEA) are of particular interest. Recently, LEA proteins have been isolated and identified in a number of plants, such as Stipa purpurea (Yang et al, 2014), Malus domestica (Liang et al, 2012), Saussurea involucrate (Qiu et al, 2014), Ammopiptanthus mongolicus (Sun et al, 2013), Prunus mume (Du et al, 2013), and Quercus robur (Sunderlíková et al, 2009). Based on sequence similarities, LEA proteins have been divided into seven categories (Dure et al, 1989;Hundertmark and Hincha, 2008;Hunault and Jaspard, 2010).…”
Section: Introductionmentioning
confidence: 99%